Spectroscopic analysis of fragment products from gamma irradiated poly allyl diglycol carbonate. (November 2022) - Elkalashy, Sh.I.; Abd El-Kareem, Mamoun S.M.; Rashad, A.M.; Zaki, M.F.
Abstract: The investigation of fragment products, structural and optical characterizations of gamma-irradiated Poly Allyl Diglycol Carbonate (PADC) has been analyzed. Gas Chromatography–Mass Spectrometry (GC–MS), X-ray diffraction (XRD) diffractometer, Fourier Transform Infrared (FTIR) Spectroscopy and UV/Vis Spectroscopy have been applied to analyze alterations of PADC polymeric solid state track detector for the understanding the mechanisms of produced alterations by gamma-irradiation. The obtained results show that the irradiated PADC samples contain induced fragment products by gamma radiation. The GC-MS analysis shows that the pristine sample has one compound product with a clear peak of ethylene glycol (EG), but for irradiated samples two compound fragmentation products appeared ethylene glycol (EG) and diethylene glycol (DEG) with different areas %. This is theoretically confirmed, by density functional theory (DFT) using Spartan'20 parallel suite for PADC in neutral and ionized states. The XRD results reveal that the molecules ordering/disordering of irradiated samples have been influenced by gamma exposure according to the values of exposure doses. This increase in disordering is due to the degradation of the polymer chains. An induced change in the band intensities have been observed in FTIR spectra, which indicate to the cleavage in the C–H bond after irradiation. The optical properties studies illustrate that significant modification in the band gap energies after irradiation. Highlights: GC-MS spectroscopy has been used to determine the fragment products of gamma irradiated PADC polymer. The GC–MS technique is a powerful tool in the investigation of the fragment products induced by radiation. XRD pattern of PADC shows that the intensity of peak is influenced according to the values of gamma doses. FT-IR analysis shows amendments in the intensity upon gamma-irradiation. An enhancement was observed in the optical properties of irradiated PADC films.